Develop An Analytical and Design Methodology for Multidimensional Databases for Data Warehouses Dr. Ihab Aldibaja - الديباجة, ايهاب (Latakia University Journal -Engineering Sciences Series, 2022)
The complexity of business in companies has increased and the amount of data that these companies deal with has increased, and normal database systems are no longer able to meet the requirements of the decision maker in terms of speed, accuracy and the volume of data that they can deal with, so the idea of ​​data warehouses has emerged, which is one of the most powerful tools Decision support systems DSS, and the urgent need for them has emerged in major companies, as each of these companies manages its own independent databases (marketing, financial...) which include a lot of shared data and the company’s need requires finding all the data related to a specific topic, such as customers, for example. By searching in one database instead of searching in different databases Data warehouses are easier for the user in terms of querying and understanding than relational databases that are designed to handle many operations. In this paper, we discuss the development of an analytical and design methodology for building data warehouses, where we define the stages and basic questions to be asked at each stage in order to reach a data warehouse that meets the needs of the organization and allows answering the required queries The results showed that following the methodology presented in the research led to shortening the time needed to build the data warehouse and reducing the time and size of modifications required to reach the final result.